2019
DOI: 10.1177/0145561319849946
|View full text |Cite
|
Sign up to set email alerts
|

Betahistine in the Treatment of Peripheral Vestibular Vertigo: Results of a Real-Life Study in Primary Care

Abstract: The present research was carried out with the objective to establish the clinical effect and safety of betahistine (48 mg daily), for the management of peripheral vestibular vertigo, in patients treated by primary care physicians in Colombia. An observational prospective cohort study was conducted including patients older than 15 years with clinical diagnosis of peripheral vestibular vertigo who were candidates to be treated with betahistine (48 mg daily). A sample size of 150 individuals was calculated, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…While a general therapeutic effect of betahistine in acute peripheral vestibular syndrome was indicated by studies in various animal models ( 33 35 ), the verdict on the strength of this effect seems to vary ( 36 ). The key to understanding the potentially ambiguous effects of betahistine seems to be its specific metabolism and pharmacokinetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…While a general therapeutic effect of betahistine in acute peripheral vestibular syndrome was indicated by studies in various animal models ( 33 35 ), the verdict on the strength of this effect seems to vary ( 36 ). The key to understanding the potentially ambiguous effects of betahistine seems to be its specific metabolism and pharmacokinetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of betashistine on symptom relief has been well studied in previous studies. 15,19 Della Pepa et al indicated the importance of objective physical examination and laboratory findings on treatment planning with be- 20 However, in a study conducted with 13 countries, it was shown that two-thirds of the subjects diagnosed with vertigo were prescribed betahistine as a result of the initial evaluation, regardless of the etiology. 21 In our study, consistent with the literature, clinicians mostly decide the treatment plan according to the general symptoms of the patients rather than objective laboratory findings.…”
Section: Discussionmentioning
confidence: 99%
“…17 Although repositioning maneuvers (RPM) are generally preferred in the treatment, it has been observed in various studies that combined treatment with drugs has better outcomes. 8,14,[18][19][20] As a result of our study, it was observed that 44.8% of the participants tended to apply RPM alone, while 22.7% prefer medical treatment and RPM together in the treatment of BPPV.…”
Section: Discussionmentioning
confidence: 99%
“…As an agonist of the histamine H1 receptor and antagonist of the histamine H3 receptor, it reduces activation of the vestibular nuclei and increases cerebral blood flow through vasodilation. This mechanism is believed to improve central compensation for vertigo (21,(64)(65)(66). Various dosages ranging from 2 mg/kg to 100 mg/kg have been reported in the literature, each showing positive effects on vertigo but not specifically in patients with IVS (67,68).…”
Section: Discussionmentioning
confidence: 99%